Ekonomi Islam dalam teori AL-Kasb Imam Al-Syaibani - Najamuddin, Najamuddin (Syari'ah, 2021)
Al Asyaibani defines al kasb (work) as an effort to find wealth in various lawful ways and economic issues are mandatory worship (fardu ain or Fardu Kipayah) that must be known by Muslims, both in terms of job clarification, natural resource management, production orientation, Utilities, business ethics, so that Al Syaibani gives a sign in whatever Islamic economy is being pursued in the world, don't forget to hope for Allah's blessing (halalan Tayyiban) and clarify economic business into four (Rental, Trade, Agriculture and Industry) and the business sector which should be prioritized is the agricultural sector, because agriculture is a business sector that produces various basic human needs that are very supportive in carrying out various obligations.